Clinical Characteristic Myasthenia Gravis among Indonesians - Syahrul Syahrul; Endang Mutiawati; Nur Astini; Nurul Fajri; Suherman Suherman (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
Myasthenia gravis (MG) is a relatively rare autoimmune disorder on peripheral nerves where an antibody of nicotinic acetylcholine postsynaptic receptor is formed on neuromuscular junction (NMJ). MG is clinically characterized with a fluctuating muscle weakness. The incidence rate is 0.25 to 2.0 per 1,000,000 among population. 10% of the population is children and adolescents.  Over the past forty years, a mortality rate has improved in the myasthenic crisis from 75% to less than 5%. Moreover, in Indonesia, this is still considered a rare disease. This study applied a retrospective cross-sectional study design. Data were gathered from patients diagnosed and treated for myasthenia gravis admitted in the neurological emergencies in the hospital during January to November 2019. Afterwards, the follow-up clinical information was also being analyzed. 12 cases of myasthenia gravis were collected with females predominated (75%), and one male (25%) with the average age of 30-40 years. The majority (75%) had the onset of < 35 years. The patients were from various districts, with 75% referral from the district and 58% housewives. Clinically, 8% patients had the ocular myasthenia and 92% was the generalized one. The ocular myasthenia had a relatively earlier onset. As MG symptomatology bears a wide range of variability and severity, it was graded based on Osserman’s and Myasthenia Gravis Foundation of America’s (MGFA) classification. Out of all patients, 13.7% belonged to Osserman’s class 1-3 (33%) and class 4-5 (67%). Myasthenia Gravis Foundation of America (MGFA) grading calibrated the severity of each crisis. The findings were 17% crisis of milder degree and 83% of moderate to severe nature. The thyroid disorder was evident in one of the patients (8.3%). Laboratory findings were 75% patients with the increase in leukocyte count. The treatment was only 25% anticholinesterase, 50% anticholinesterase and steroid, in addition to 25% anticholinesterase and therapeutic plasma exchange (TPE). The hospital stay was (the average in days) 83% with >7 days. The myasthenia gravis reported was 12 cases. Patients’ outcome depended on the clinical condition when they first arrived in the hospital. These findings will be useful for the resource allocation and planning in health services. Many regions worldwide have few or no epidemiological data on the myasthenia gravis, and more studies are required to yield more estimates that are accurate.